Malakok: Suatu Mekanisme Pendamai Ala Minangkabau - Eriyanti, Fitri (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2007)
Conflict often occured when two ethnic groups or more clashed. Some of the ethnic group conflicts occured in Indonesia, but in the case of West Sumatera the conflict rarely occured, especially among the community of Minangkabau. Some ethnic groups from different culture have come to and live in Minangkabau area and generally they can live together with Minangkabau people in peace and savely. Some of the ethnic groups integrate with Minangkabau community through a tradition called â€œMalakokâ€. Â Kata Kunci: Malakok, kelompok etnik, Minangkabau, struktur sosial, konflik, integrasi.